UV-Exposure effect on the mechanical properties of PEO/PVA blends - Almashhadani, Nahida Joumaa Hameed (Iraqi Journal of Science, 2021)
Poly ethylene oxide PEO / Poly vinyl alcohol PVA blends were prepared by cast method at different ratios of (25%PEO/75%PVA, 30%PEO/70%PVA, 35%PEO/65%PVA, 40%PEO/60%PVA, and 50%PEO/505PVA). Samples miscibility ,and thermal stability were studied by using differential scanning calorimetry(DSC),and thermo gravimetric analysis (TGA) analysis. The results proved that there was one glass transition temperature (Tg=160°C) at 25%PEOratio)that was attributed to its miscibility. This miscibility associated with (Hydrogen bonds) between (Hydroxyl group) in PVA, and PEO, whereas there were two glass transition temperature for the blends ratio more than 30%PEO,that was due its immiscibility. The results proved increase in glass transition temperature (Tg) with PEO loading increase: whereas the melting point was fixed about(Tm=310°C). TGA results showed that PEO loading caused overlapping between degradation stages ,and shifting in the second stage to higher degradation temperature, that was due to the good PVA, and PEO compatibility, and thermal stability improved of polymer blends. The mechanical properties of the samples involved were studied :it was found that the tensile strength decreased with PEO ratio increase: whereas ,the elongation at break increased with PEO ratio . 25% PEO/PVA proved better tensile strength than the others blend ratios and elongation-at-break values in comparison with that ratio more than 25%,which was due to good miscibility. These results were enhanced with optical microscope and FTIR analysis. 25%PEO/PVA was sellected to study the UV-Weathering effect on the mechanical properties according to its ultimate strength(26.67MPa) in comparision with the blends envolved.The stress strain curves for 25%PEO/PVA before and after UV-Weathering with periods of time(25,60,and 90Hr.) showed little changes in ultimate strength up to (60Hr) exposure time,then there were little decrese in ultmate strength in(90Hr) exposure time . Ultimate tensile strength decrease was attributed to premature failur induced by polymer photo degradation. UV-Weathering caused yelowish of exposed samples that was due to long chain conjugated polymer sequencesbond formation induced by oxidative photo degradation . The results proved little changes within (60Hr),that was attributed to polymer stability.It was folowed by little changes in tensile strength and the elongation at break decreased that was due to sample brittlence increase,which was induced by irradiation ,that caused modulus of elasticity increase. It was experimentally observed that the value of thermal conductivity of (PVA= 0.099W/cm.K).The results proved decrease in thermal conductivity with PEO loading increase.